1997
DOI: 10.1002/j.2050-0416.1997.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterisation of Beer Polypeptides Derived From Barley Hordeins

Abstract: Two groups off hordein-reactive antibodies (cross-reactive in barley with B/C monomers or subunits from the B/D-hordein aggregates) were used for the analysis of malt, wort and beer. A number of additional lower molecular weight hordein-derived polypeptides were present in water extracts of malts and worts, and protease inhibitors or higher mash-in temperature had a stabilising effect on certain hordein-derived polypeptides.The solubilisation profiles of hordein polypeptides monitored by specific immunological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 25 publications
0
24
0
2
Order By: Relevance
“…It is important to note that colour is closely associated with proteins and peptides, especially those of higher molecular weight. This is an interesting finding as most haze formation is considered to be the result of oxidation of beer phenols (presumably free), followed by polymerisation and association with hydrophobic proteins 8,23,26 . In contrast, these results suggest that the phenol association with protein precede further oxidation of either the sulfhydryl groups or phenol-protein or peptide derivatives that lead to polymerisation and beer haze formation.…”
Section: )79087 %2( (-7'977-32mentioning
confidence: 97%
See 2 more Smart Citations
“…It is important to note that colour is closely associated with proteins and peptides, especially those of higher molecular weight. This is an interesting finding as most haze formation is considered to be the result of oxidation of beer phenols (presumably free), followed by polymerisation and association with hydrophobic proteins 8,23,26 . In contrast, these results suggest that the phenol association with protein precede further oxidation of either the sulfhydryl groups or phenol-protein or peptide derivatives that lead to polymerisation and beer haze formation.…”
Section: )79087 %2( (-7'977-32mentioning
confidence: 97%
“…Hydrophobicity and molecular weight of these proteins have been identified as the two most important attributes of proteins and peptides involved in foam formation and retention as well as haze formation [7][8][9][21][22][23]26,27,29 . Hydrophobic polypeptides of lower molecular weight (5 to 30 × 10 3 ) were found to enhance foam formation and retention 8,23,26 . In contrast, colloidal instability and haze formation were associated with high molecular weight hydrophobic polypeptides 8,23 .…”
Section: -2863(9'8-32mentioning
confidence: 99%
See 1 more Smart Citation
“…Kauffman et al (1994), using monoclonal antibodies, identified the presence of D and B hordein components in lager foam, whereas C hordein components could not be detected. ELISAs have also been used to identify polypeptides derived from B, C, and D hordein in beer and beer foam (Sheehan and Skerritt 1997). Although large proline-rich polypeptides influence chill haze formation (Asano et al 1982), smaller hydrophobic polypeptides have positive effects on foam formation.…”
Section: Hordeins Malting and Brewing Qualitymentioning
confidence: 99%
“…For example the Finnish Coeliac Society cannot recommend beer for coeliacs. Studies have shown that barley prolamins, or hordeins, decrease in amount during brewing 6,12 . Wheat beers contain wheat prolamins, gliadins, or prolamin peptides as degradation products of wheat.…”
Section: Introductionmentioning
confidence: 99%